Conduction of a round-robin test on a real sample for the identification of gunshot residues by SEM/EDX. (April 2020) - Charles, Sébastien; Dodier, Thierry; Kaindl, Monika; Kastéropoulos, Alain; Knijnenberg, Alwin; Larsson, Marcus; Lauper, Sandrine; Merat, Nadine; Niewoehner, Ludwig; Scholz, Thomas; Simon, Laurence
Highlights: A round-robin test was conducted on a real sample for GSR analysis by SEM/EDX. Eleven Institutes participated to this test. With regard to the allocation to a specific GSR-class, a broad consensus emerged for ca. 75% of the particles of interest. This type of campaign definitely offers a tool to monitor and optimize the classification process of the SEM/EDX systems. Abstract: A round-robin test on the identification of GSR particles by SEM/EDX and involving eleven Institutes was conducted on a real sample, in order to evaluate the possibilities/limitations of using such sample to get additional information (compared to the analysis of the usual synthetic sample used within the framework of the ENFSI proficiency test) about the performances of the SEM/EDX systems. Each Institute was asked to analyse this sample following its own standard operating procedure, and by using all the systems in house, whenever available. Between each Institute, a check of the sample was performed by the organizing Institute (NICC), in order inter alia to monitor any degradation and/or contamination of the sample. A total of about 30 analyses were performed on the sample. For each particle of interest identified on the real sample, the detection effectiveness was monitored, as well as the classification allotted by each Institute. The Institutes were also asked to report some of their measurement parameters, and to send the results as they would have been communicated in their own case report. A quite good agreement was observed with regard to the classification of the particles of interest, since a broad consensus was reached for approximately 75% of these particles. A different classification risk exists for some classes, the barium/antimony classes being probably the most critical, as traces of lead may cause the particles to shift (or not) from the consistent with GSR upper-class to the characteristic of GSR upper-class; in the end, the decision to shift from one class to another strongly depends on local rules. At the end of the campaign, a survey sent to collect experience and lessons learned from this exercise showed that analysing a real sample definitively offers an added value, especially in terms of classification process (during the automatic run and when performing the manual review) of particles.